2016
DOI: 10.1007/s11999-015-4523-3
|View full text |Cite
|
Sign up to set email alerts
|

What Factors are Associated With a Surgical Site Infection After Operative Treatment of an Elbow Fracture?

Abstract: Background Surgical site infections are one of the more common major complications of elbow fracture surgery and can contribute to other adverse outcomes, prolonged hospital stays, and increased healthcare costs. Questions/purposes We asked: (1) What are the factors associated with a surgical site infection after elbow fracture surgery? (2) When taking the subset of closed elbow fractures only, what are the factors associated with a surgical site infection? (3) What are the common organisms isolated from an el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 31 publications
4
16
0
5
Order By: Relevance
“…4). These findings correspond with smokers' enhanced susceptibility to clinical S. aureus infections and postoperative S. aureus-mediated complications (28,33). Combined with the observation that month-long carriers of experimentally inoculated S. aureus also presented higher natural nasal S. aureus loads (Fig.…”
Section: Smoking Cessation Decreases Nasal S Aureus Load Infection Asupporting
confidence: 77%
See 1 more Smart Citation
“…4). These findings correspond with smokers' enhanced susceptibility to clinical S. aureus infections and postoperative S. aureus-mediated complications (28,33). Combined with the observation that month-long carriers of experimentally inoculated S. aureus also presented higher natural nasal S. aureus loads (Fig.…”
Section: Smoking Cessation Decreases Nasal S Aureus Load Infection Asupporting
confidence: 77%
“…Some studies associated smoking and secondhand smoke with increased S. aureus carriage rates (20)(21)(22)(23), and others declared no association (24,25), while the TromsĂž (Norway) Staph and Skin Study 2007-08 indicated that smoking might be protective (26). Notably, S. aureus carriage triples the risk for postoperative skin and soft tissue infections (27), and smoking associates with higher infection rates (28). In the current study, we determined the nasal S. aureus carriage rate in healthy smokers who attend the University of Central Florida (UCF).…”
mentioning
confidence: 99%
“…The problem becomes clear when reviewing the clinical literature. Some studies have cited the CDC-guidelines without a specific description of osteomyelitis [19,20]; others use these guidelines but include their own additional inclusion criteria such as purulent drainage or other clinical signs [21]. Perhaps due to the lack of suitable definitions for trauma patients, there are also authors who do not define infection [22] and others who provide a unique custom-made definition [23].…”
Section: Definitionmentioning
confidence: 99%
“…Cigarette smoking has a negative impact on wound healing in orthopedic surgery with an increase in the incidence of SSI of 7% [4]. Many authors have also confirmed an increase in SSI after plastic surgery using multivariate analysis and shown that smoking suppresses the immune system [5]. Numerous studies have confirmed it as a complication for wound healing in terms of necrosis and infections due to the vasoconstricting and deoxygenating effects of nicotine and other tobacco-related chemicals.…”
Section: Future Directions To Limit Surgical Site Infectionsmentioning
confidence: 99%